PENGARUH BRAND IMAGE DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PRODUK WARDAH DI TOKO MY LOVA KOTA BENGKULU - Pamisti, Nensy; Arini, Eti (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2024)
This study aims to determine "The Influence of Brand Image and Promotion on Consumer Purchasing Decisions on Wardah Products at My Lova Store in Bengkulu City", both partially and simultaneously. The type of research used is quantitative research. The population in this study is consumers of Wardah products at the My Lova Store in Bengkulu City, using a non-probability sampling technique, which means that samples are taken randomly, namely consumers who visit the Wardah product stand at the My Lova Store in Bengkulu City. Based on the results of these tests, the brand image variable has a positive and significant effect on consumer purchasing decisions. Promotional variables have a positive and significant effect on consumer purchasing decisions. Brand image and promotion together have a positive and simultaneous effect on the purchase decision variable. Keyword: Brand Image, Promotions, Purchase Decisions